Investigation of Anti-cancer Properties of 2,2,4,4-Tetra (4?-oxy-substituted-chalcone)-6,6-diphenylcyclotriphosphazene Derivatives Against Human Ovarian (A2780) and Prostate (PC-3) Cancer Cell Lines - Tekin, Cigdem; Koran, Kenan; Tekin, Suat; Sandal, Suleyman; Gorgulu, Ahmet Orhan (Wiley-Blackwell, 2016)
[Abstract Not Available]